Intermittent cardiac overload results in adaptive hypertrophy and provides protection against left ventricular acute pressure overload insult. (23rd June 2015) - Moreira‐Gonçalves, Daniel; Henriques‐Coelho, Tiago; Fonseca, Hélder; Ferreira, Rita; Padrão, Ana Isabel; Santa, Cátia; Vieira, Sara; Silva, Ana Filipa; Amado, Francisco; Leite‐Moreira, Adelino; Duarte, José Alberto
Abstract : Key points: The present study aimed to test whether a chronic intermittent workload could induce an adaptive cardiac phenotype Chronic intermittent workload induced features of adaptive hypertrophy This was paralleled by protection against acute pressure overload insult The heart may adapt favourably to balanced demands, regardless of the nature of the stimuli. Abstract: The present study aimed to test whether submitting the healthy heart to intermittent and tolerable amounts of workload, independently of its nature, could result in an adaptive cardiac phenotype. Male Wistar rats were subjected to treadmill running (Ex) ( n  = 20), intermittent cardiac overload with dobutamine (ITO) (2 mg kg –1, s.c. ; n  = 20) or placebo administration (Cont) ( n  = 20) for 5 days week –1 for 8 weeks. Animals were then killed for histological and biochemical analysis or subjected to left ventricular haemodynamic evaluation under baseline conditions, in response to isovolumetric contractions and to sustained LV acute pressure overload (35% increase in peak systolic pressure maintained for 2 h). Baseline cardiac function was enhanced only in Ex, whereas the response to isovolumetric heartbeats was improved in both ITO and Ex. By contrast to the Cont group, in which rats developed diastolic dysfunction with sustained acute pressure overload, ITO and Ex showed increased tolerance to this stress test. Both ITO and Ex developed cardiomyocyte hypertrophy without fibrosis, no overexpression of osteopontin‐1 or β‐myosin heavy chain, and increased expression of sarcoplasmic reticulum Ca 2+ protein. Regarding hypertrophic pathways, ITO and Ex showed activation of the protein kinase B/mammalian target of rapamycin pathway but not calcineurin. Mitochondrial complex IV and V activities were also increased in ITO and Ex. Chronic submission to controlled intermittent cardiac overload, independently of its nature, results in an adaptive cardiac phenotype. Features of the cardiac overload, such as the duration and magnitude of the stimuli, may play a role in the development of an adaptive or maladaptive phenotype. Abstract :